Nrg1/ErbB signaling‐mediated regulation of fibrosis after myocardial infarction. Issue 2 (8th January 2022) - Shiraishi, Manabu; Yamaguchi, Atsushi; Suzuki, Ken
Abstract: Appropriate fibrotic tissue formation after myocardial infarction (MI) is crucial to the maintenance of the heart's structure. M2‐like macrophages play a vital role in post‐MI fibrosis by activating cardiac fibroblasts. Because the mechanism by which post‐MI cardiac fibrosis is regulated is not fully understood, we investigated, in vitro and in vivo, the cellular and molecular mechanisms of post‐MI fibrotic tissue formation, especially those related to the regulation of cellular senescence and apoptosis. CD206 + F4/80 + CD11b + M2‐like macrophages collected from mouse hearts on post‐MI day 7 showed increased expression of neuregulin 1 (Nrg1). Nrg1 receptor epidermal growth factor receptors ErbB2 and ErbB4 were expressed on cardiac fibroblasts in the infarct area. M2‐like macrophage‐derived Nrg1 suppressed both hydrogen peroxide‐induced senescence and apoptosis of fibroblasts, whereas blockade of ErbB function significantly accelerated both processes. M2‐like macrophage‐derived Nrg1/ErbB/PI3K/Akt signaling, shown to be related to anti‐senescence, was activated in damaged cardiac fibroblasts. Interestingly, systemic blockade of ErbB function in MI model mice enhanced senescence and apoptosis of cardiac fibroblasts and exacerbated inflammation. Further, increased accumulation of M2‐like macrophages resulted in excessive post‐MI progression of fibrosis in mice hearts. The molecular mechanism underlying the regulation of fibrotic tissue formation in the infarcted myocardium was shown in part to be attenuation of apoptosis and senescence of cardiac fibroblasts by the activation of Nrg1/ErbB/PI3K/Akt signaling. M2‐like macrophage‐mediated regulation of Nrg1/ErbB signaling has a substantial effect on fibrotic tissue formation in the infarcted adult mouse heart and is critical for suppressing the progression of senescence and apoptosis of cardiac fibroblasts.